Utilization of Yam Bean Juice as Nutrient Source for Bacterial Cellulose Production by Komagataeibacter nataicola TISTR 975 - Chaiyachet, Orn A.; Thongmoon, Sucheera; Udomchai, Tharintorn (Current Nutrition & Food Science, 2023)
Background: Bacterial cellulose has attracted much interest over the years because of its diverse applications stemming from its unique properties. Alternative sources of raw materials for culture medium have become essential to reduce the cost of raw materials and scale up bacterial cellulose production. Objectives: The present study aims to investigate the cellulose-producing ability and characteristics of bacterial cellulose produced by Komagataeibacter nataicola TISTR 975 using yam bean juice as a nutrient source and optimizing the culture medium conditions to produce bacterial cellulose. Methods: Bacterial cellulose was produced by K. nataicola TISTR 975 using yam bean juice as the nutrient source in the culture medium. Fermentation was performed in static culture using 10% inoculum, with varying levels of initial total soluble solids content (8, 10, and 12 °Brix), supplemented with ammonium sulfate (0.1, 0.3, and 0.5 (% w/v)), pH 5.0, 1.4% (v/v) ethanol, and incubated at 30 °C for 10 days. The cellulose membrane was measured for cellulose yield. Physicochemical and sensory characteristics of bacterial cellulose were examined. Results: Initial total soluble solids content at 10 °Brix (equal to the sugar content of approximately 100 g/L) and supplemented with 0.1% (w/v) of ammonium sulfate improved bacterial cellulose yield. Moisture content and water holding capacity (WHC) of bacterial cellulose were high, and L*, a*, and b* values and textural properties were related to perceived sensory characteristics. Sensory evaluation showed the highest score for color and overall acceptability. Conclusion: Local edible yam bean tubers could be used as an alternative raw material for bacterial cellulose production by K. nataicola TISTR 975 using yam bean juice, and bacterial cellulose produced using yam bean juice as a nutrient source has the sensory attributes consistent with the desirable characteristics of raw material for food and processed food products.
Keywords: Komagataeibacter nataicola